2006
DOI: 10.1105/tpc.106.041012
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis LHT1 Is a High-Affinity Transporter for Cellular Amino Acid Uptake in Both Root Epidermis and Leaf Mesophyll

Abstract: Amino acid transport in plants is mediated by at least two large families of plasma membrane transporters. Arabidopsis thaliana, a nonmycorrhizal species, is able to grow on media containing amino acids as the sole nitrogen source. Arabidopsis amino acid permease (AAP) subfamily genes are preferentially expressed in the vascular tissue, suggesting roles in long-distance transport between organs. We show that the broad-specificity, high-affinity amino acid transporter LYSINE HISTIDINE TRANSPORTER1 (LHT1), an AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
372
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(404 citation statements)
references
References 70 publications
28
372
0
4
Order By: Relevance
“…utes to the root import of several amino acids (19,20), might also be involved in m-tyrosine uptake from the medium. Inhibition of the shikimate pathway enzyme 3-deoxy-Darabino-heptulosonic acid 7-phosphate synthase by m-tyrosine in E. coli (21) suggested that similar effects could produce toxicity in plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…utes to the root import of several amino acids (19,20), might also be involved in m-tyrosine uptake from the medium. Inhibition of the shikimate pathway enzyme 3-deoxy-Darabino-heptulosonic acid 7-phosphate synthase by m-tyrosine in E. coli (21) suggested that similar effects could produce toxicity in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous solution of commercial m-tyrosine (10,20,40,80, and 160 M concentrations) or 1 ml of an aqueous solution of dried Intrigue root exudates extract adjusted to contain m-tyrosine at identical concentrations, as determined by HPLC, were spotted onto filter paper. Root growth of L. sativa and D. sanguinalis (10 seedlings per Petri dish) were measured after 5 days (L. sativa) or 7 days (D. sanguinalis) and compared with the lengths of root and shoot of control plants grown on plates treated only with 1 ml water.…”
Section: Comparison Of the Phytotoxic Activities Of M-tyrosine And Rootmentioning
confidence: 99%
“…Tissue-specific overexpression of this transporter in the Arabidopsis root tip led to increased proline content of the root apex (0-5 mm) and increased growth under control conditions (Ueda et al, 2008), although the effects of such targeted overexpression on growth under stress conditions were not tested. Whether or not this function in Arabidopsis is performed by one of the ProTs, other transporters known to have proline uptake activity in roots such as LHT1 or AAP5 (Hirner et al, 2006;Rentsch et al, 2007;Svennerstam et al, 2008), or other yet uncharacterized transporters will be an interesting question for further experiments. Long distance proline transport may be important in taking proline produced in photosynthetic tissue as a way to buffer cellular redox status and moving it to non-photosynthetic tissue such as roots, where it can contribute to osmotic adjustment or be catabolized to support growth ( Figure 5A; see sections IV.-A.…”
Section: B Intercellular Transportersmentioning
confidence: 99%
“…In Arabidopsis roots, the three amino acid transporters AAP1, AAP5 and LHT1 have been shown to play a role in amino acid uptake. They each have different specificity and affinity for amino acids (Hirner et al, 2006;Lee et al, 2007;Svennerstam et al, 2008). Amino acid transporters are less well characterised in other species but it is well documented that amino acid uptake occurs in a wide range of species including gymnosperms (Nasholm et al, 1998;Persson and Nasholm, 2002), dicots (Ge et al, 2009;Kielland, 1994;Nasholm et al, 1998Nasholm et al, , 2000Streeter et al, 2000) and monocots (Biernath et al, 2008;El-Naggar et al, 2009;Henry and Jefferies, 2003;Jamtgard et al, 2008Jamtgard et al, , 2010Kielland, 1994;Lipson et al, 1999;Nasholm et al, 1998Nasholm et al, , 2000Nasholm and Persson, 2001;Schimel and Chapin, 1996;Streeter et al, 2000;Thornton, 2001;Thornton and Robinson, 2005;Yamagata and Ae, 1999).…”
Section: E Gioseffi Et Al: Organic and Inorganic N Interactions Inmentioning
confidence: 99%